Effect of irradiation on malignant tumour invasion into bone - Kathawut Tachasuttirut (2018)
Objective: The periosteum acts as a protective harrier against the entry of tumour cells during direct bone invasion of malignant tumours. Injuries to the periosteum may cause impairment of its barrier function. The effect of irradiation on tumour bone invasion was examined using a mouse tumour transplantation model. Materials and Methods: Forty four C57BU6J mice were used to evaluate the effect of irradiation. The calvarias of the mice were scratched and/or irradiated (dose, 10 Gy), and B16F10 melanoma cells were inoculated. Mice from the irradiation only group were inoculated with B16F10 cells 1, 7 or 14 days after irradiation, and the association of irradiation effects with this duration was evaluated. Calvaria specimens were radiologically and histologically evaluated, and the quantity of bone resorption was examined Results: Bone invasion was not evident in non-irradiated non-scratched control mice, even whe the tumour size reached 15 to 20 mm. However, cortical bone resorption and tumour cell entry were observed in both irradiation only and scratch only groups. More aggressive invasion of B16F10 was found in irradiation plus scratch calvarias. Evaluation based on sagittal suture opening revealed no significant differences in bone invasion among these groups Conclusions: Injuries caused by irradiation made the periosteum more prone to malignant tumour invasion. The effect of irradiation on bones might be long lasting. © 2008 Asian Association of Oral and Maxillofacial Surgeons.